Relationship between chemical dependents, blood pressure values and Dentist Surgeon performance (Research, Society and Development, 2020)
The abuse of drugs, legal or illegal, is one of the main social and public health problems in the world, so the contact of the dental surgeon with patients dependent on these substances is inevitable. Studies suggest that drug use increases oral manifestations, such as changes in salivary flow, dental wear, caries, periodontal disease, dry mouth, and pain. Therefore, the professional must be prepared to assist these patients and be aware of the limitations and possible interactions, especially in invasive treatments, whether in a hospital environment with the sedated patient or in the office with local anesthetics. The objective of this work is to report a case of monitoring blood pressure, oxygen saturation and heart rate, during a procedure with multiple extractions in a chemical dependent patient. Although the patient remained stable, there was an increase in diastolic pressure in the postoperative period, which may be related to the vasoconstriction caused by the use of marijuana and crack, and the action of the anesthetic's epinephrine. This increase is related to changes in the sympathetic and parasympathetic system, which is why the importance of knowing the substances used in the procedure and in prescription drugs. It is concluded that it is necessary to improve the knowledge of the physiological, chemical and neurological changes that involve these patients, for a safe dental treatment, and when necessary in conjunction with a multi-professional team, to know how to refer the patient and identify health problems that are not only oral.